Intensive and Critical Care Nursing of a COVID-19 Patient in Turkey A Case Study - Yıldırım, Dilek; Genç, Zeliha (Lippincott Williams and Wilkins, 2022)
Background A multidisciplinary approach is required to provide holistic care and treatment in the fight against the COVID-19 pandemic. Being in the center of the multidisciplinary approach, nurses provide therapeutic, primary, and psychosocial care for the patients. Objectives This study was conducted to diagnose according to the North American Nursing Diagnosis Associations by determining the care needs of a case who was diagnosed with COVID-19, planning interventions, and observing the results. Methods This descriptive case study included a patient who applied to a university hospital located in Istanbul/Turkey between March and April 2020 because of COVID-19. As the inclusion criteria, only a positive result from a polymerase chain reaction test was accepted. The details of the patient presented in the study were obtained through face-to-face interviews and electronic medical records. Discussion Specified care plans enable defining problems in practice for all needs of the individual and developing solution recommendations. It was observed that there were improvements and a decrease in symptom severity after the interventions were applied for the symptoms developing in the case. The execution of the treatment and care practices under quality and effective nursing care such as giving proper ventilatory support at the right time, giving prone position for a long time, and providing sufficient fluid resuscitation and an early and balanced diet contributed to the patient's discharge from the intensive care unit successfully without having any organ dysfunction. This presentation is expected to be a source for collaborative nursing care for other cases diagnosed with COVID-19 and intensive care indications. Conclusions Nursing care interventions were applied for gas exchange, risk of decreased tissue perfusion, excess fluid volume, and constipation nursing diagnosis. It was observed that there were improvements and a decrease in symptom severity after the interventions were applied for the symptoms developing in the case. This presentation is expected to be a source for collaborative nursing care for other cases diagnosed with COVID-19 and intensive care indications.
Keywords: Clinical care; COVID-19; Critical care; Intensive care; Nursing care